Factors Contributing to Academic Boredom among English-Major Students at Nong Lam University Ho Chi Minh City, Vietnam (Journal of Contemporary Educational Policies and Practices, 2024)
Academic boredom can detrimentally impact students' motivation, engagement, and academic performance. Recognizing the challenges faced by English-major students at Nong Lam University, Ho Chi Minh city, the authors of this paper conducted a study to investigate the underlying factors contributing to academic boredom within this specific academic context. A quantitative research method was employed in the current study to investigate the antecedents of academic boredom among the English-majored students. The population of this study consists of 427 English language majors at Nong Lam University, Ho Chi Minh City, Vietnam. A convenience sampling method was utilized. Correlation and regression analyses were used to explore the relationships between the antecedent factors and academic boredom among students. The findings reveal a combination of internal and external factors contributing to boredom. It was also found that the most common causes of boredom are the students’ attitude toward their learning and the university’s environment while no significant correlation was observed between the level of boredom and teaching contents, teaching methods and pedagogical style. Some implications concerning how to reduce EFL classroom boredom are also presented in this paper.
Keywords: Academic boredom; antecedents; EFL students; students’ attitude; university’s environment